2015
DOI: 10.1590/s0100-204x2015000100003
|View full text |Cite
|
Sign up to set email alerts
|

Respostas ecofisiológicas de cafeeiros submetidos ao deficit hídrico para concentração da florada no Cerrado de Minas Gerais

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de diferentes períodos de imposição do deficit hídrico sobre a concentração da florada do cafeeiro (Coffea arabica), bem como sobre as trocas gasosas, a produtividade, a maturação e a qualidade dos grãos. As cultivares Catuaí Vermelho IAC 144 e Bourbon Amarelo J9 foram avaliadas conforme os seguintes tratamentos: não irrigado (NI), irrigado continuamente (IC), e suspensão da irrigação em 1/7/2010 (D1) e em 1/8/2010 (D2), com retorno desta em 24/9/2010. Cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…The observed reduction in leaf water potential may be related to the sugars accumulation in leaves, which together with other physiological mechanisms, such as stomatal closure and reduced transpiration, contribute to the maintenance of tissue hydration. Other species also showed reduced water potential when under conditions of low water availability (Ronchi et al, 2015, Mota & Cano, 2016.…”
Section: Plant Water Relationsmentioning
confidence: 99%
“…The observed reduction in leaf water potential may be related to the sugars accumulation in leaves, which together with other physiological mechanisms, such as stomatal closure and reduced transpiration, contribute to the maintenance of tissue hydration. Other species also showed reduced water potential when under conditions of low water availability (Ronchi et al, 2015, Mota & Cano, 2016.…”
Section: Plant Water Relationsmentioning
confidence: 99%
“…At 90 days, the values were -0.2 and -1.8 MPa for treatments irrigated permanently and not irrigated. Ronchi et al (2015) found values of leaf water potential in the Catuaí Red IAC 144 cultivar of -0.10, -0.35, -0.5 and -0.6 MPa for treatments irrigated continuously, 30 days of irrigation suspension, 60 days of irrigation suspension and non-irrigated, respectively. The results found by these authors diverge, in parts, from the values estimated by the equation of the suggested line, however, the edaphoclimatic conditions and the crop management in each study affect the rate of water use by the plants, thus altering their water potential.…”
Section: Resultsmentioning
confidence: 88%
“…Several studies have verified that there is a dependence between the leaf water potential of the coffee tree and the soil matrix potential in different irrigation managements, however, the water potential levels found are divergent because they work in distinct and uncontrolled environments (Soares et al, 2005;Oliveira et al, 2009;Ronchi et al, 2015;Craparo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We assume that these alterations in gas exchange levels may have occurred by two paths. The first would be related to a possible reduction of the source and drain relationship in the plant, derived from the potential that IAA has in increasing the root surface of plants (Taiz et al, 2017), this development in the root system would provide an increase in the potential for water and nutrient absorption, which consequently could be associated with lower water and nutritional stresses by plants, which could provide an increase in gas exchanges (Ronchi et al, 2015;Taiz et al, 2017;Tatagiba et al, 2008).…”
Section: Discussionmentioning
confidence: 99%